Synthesis of Spherical Composite CMC-LTO-EGDE-ME for Lithium Recovery from Geothermal Water - Yingchun Xie; Yilin Zhang; Jiayu Qin; Murodjon Samadiy; Tianlong Deng (Journal of Chemistry)
In this study, ethylene glycol diglycidyl ether (EGDE) and melamine (ME) were used to prepare a spherical composite material CMC-LTO-EGDE-ME through the strategy of cross-linking reaction of biodegradable sodium carboxymethyl cellulose (CMC) with Li2TiO3 (LTO) to improve the cycle stability of the adsorption-desorption for lithium recovery. In the geothermal water at 333.15°K, the adsorption capacity of the spherical composite adsorbent for lithium-ion is 12.02 mg/g, and the adsorption equilibrium time is 8 h. There is a good selectivity of Li+ (Kd = 3.7 × 103) and high separation factors between Li+ and Na+, K+, Cs+ and Ca2+ (between 39.17 and 181.97). Studies on adsorption kinetics and adsorption isotherm showed that composite material’s adsorption process was obtained from the pseudosecond-order kinetics and the molecular diffusion model. It was found that the composite material has broad applications in lithium recovery from geothermal water.